The Questionnaire: Tools for Measuring and Evaluating Inpatient Satisfaction (Global Journal of Medical Research, 2022)
Patient satisfaction is currently at the heart of recent economic studies in hospital management It remains a goal and a challenge for all stakeholders In fact it is emerging as one of the ways to evaluate and improve the quality of care This article is inspired by the growing interest in assessing patient satisfaction as a key indicator of quality of care The objective of this article is therefore to define and identify the aspects of patient satisfaction measurement in particular the questionnaire which represents an essential measurement tool in the field
Keywords: measurement of patient satisfaction; questionnaire; quality of care; hospital world